2005
DOI: 10.1097/01.prs.0000154213.06888.f9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obesity and Volume of Resection on Success in Reduction Mammaplasty: An Outcomes Study

Abstract: The authors conclude that there is no justification for discriminating against obese patients in either the performance of breast reduction surgery or the provision of insurance coverage for the same. The authors find no justification for denial of insurance coverage for patients in whom lesser tissue volumes are to be resected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0
10

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 3 publications
4
42
0
10
Order By: Relevance
“…[50][51][52] Our results confirm this observation with high rates of overweight (35%) and obesity (35%) in our subjects with macromastia. Thus, we controlled for BMI category.…”
Section: Discussionsupporting
confidence: 80%
“…[50][51][52] Our results confirm this observation with high rates of overweight (35%) and obesity (35%) in our subjects with macromastia. Thus, we controlled for BMI category.…”
Section: Discussionsupporting
confidence: 80%
“…By doing so, we found the preoperative ptotic breast mass was significantly correlated to the resectional breast mass, while alleviating breast weight-related symptoms, achieving a pleasing breast shape, and avoiding over-or under-resection. Breast reduction can also be beneficial in the obese patient (10,11), and this technique proved to be statistically significant in the obese women (body mass index greater than 30 kg/m 2 ) in our study.…”
Section: Discussionmentioning
confidence: 73%
“…[16] Other studies similarly found no statistically significant difference in complication rates among the obese. [14,15,17] However, contradictory findings exist in the literature as well, supporting obesity as a risk factor. [6,[9][10][11][12][13] Chun et al [13] identified a threshold of BMI 35.6 at which postoperative complications were increased two-fold, the most common complication being infection.…”
Section: Discussionmentioning
confidence: 96%
“…Some studies associate obesity with increased postoperative complications, [9][10][11][12][13] whereas others find no statistically significant correlation. [14][15][16][17] In 2014, Nelson et al [6] studied obesity and reduction mammaplasty using the 2005-2011 American College of Surgeons -National Surgical Quality Improvement Program (ACS-NSQIP) datasets. NSQIP is a nationally-validated, risk-adjusted surgical outcomes database to measure and improve the quality of surgical care.…”
Section: Introductionmentioning
confidence: 99%